Application of Combined Ankle Pump Exercise and 30° Leg Elevation in Nursing Care to Reduce Leg Edema in a Patient with Chronic Kidney Disease : Case Report - Puja Sheylla Riskita Cahyani; Muhamad Zulfatul A'la; Ana Nistiandani; Yudho Tri Handoko (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2026)
Chronic kidney disease (CKD) is a global health problem with multifactorial etiologies that may clinically manifest as leg edema, affecting patient comfort and mobility. Although pharmacological and non-pharmacological therapies can be administered simultaneously, evidence regarding the application of combined ankle pump exercise and 30° leg elevation in nursing care for edema reduction in CKD patients remains limited. To analyze nursing care through the application of combined ankle pump exercise and 30° leg elevation therapy to reduce leg edema in a patient with CKD. This study employed a case report design involving a CKD patient with bilateral leg edema. Nursing interventions consisted of a combination of ankle pump exercise and 30° leg elevation administered twice daily for 8 minutes per session, accompanied by furosemide therapy. Edema was assessed through daily observation of edema grading. A reduction in edema level was observed, with the left leg showing improvement on the third day and the right leg on the fourth day, decreasing from grade II to grade I edema. The application of combined ankle pump exercise and 30° leg elevation, accompanied by furosemide administration, demonstrated a reduction in the degree of leg edema in a patient with CKD. However, further studies using larger samples and controlled study designs are needed to confirm the effectiveness and generalizability of this intervention in clinical nursing practice. Chronic kidney disease (CKD) is a global health problem with multifactorial etiologies that may clinically manifest as leg edema, affecting patient comfort and mobility. Although pharmacological and non-pharmacological therapies can be administered simultaneously, evidence regarding the application of combined ankle pump exercise and 30° leg elevation in nursing care for edema reduction in CKD patients remains limited. To analyze nursing care through the application of combined ankle pump exercise and 30° leg elevation therapy to reduce leg edema in a patient with CKD. This study employed a case report design involving a CKD patient with bilateral leg edema. Nursing interventions consisted of a combination of ankle pump exercise and 30° leg elevation administered twice daily for 8 minutes per session, accompanied by furosemide therapy. Edema was assessed through daily observation of edema grading. A reduction in edema level was observed, with the left leg showing improvement on the third day and the right leg on the fourth day, decreasing from grade II to grade I edema. The application of combined ankle pump exercise and 30° leg elevation, accompanied by furosemide administration, demonstrated a reduction in the degree of leg edema in a patient with CKD. However, further studies using larger samples and controlled study designs are needed to confirm the effectiveness and generalizability of this intervention in clinical nursing practice.